Standard Operating Protocol for Ion-Exchange Capacity of Anion Exchange Membranes - Wang, Lan; Rojas-Carbonell, Santiago; Hu, Keda; Setzler, Brian P.; Motz, Andrew R.; Ueckermann, Matthew E.; Yan, Yushan (Frontiers in Energy Research, 2022)
Ion-exchange capacity (IEC) is the measure of a material’s capability to displace ions formerly incorporated within its structure. IEC is a key feature of anion-exchange membranes (AEM), as it determines the AEM’s ability to conduct the ions required to sustain the electrochemical reactions where they are utilized. As an intrinsic property, measuring the IEC accurately is essential to study AEMs and understand their performance within devices. In this method article, a facile and accurate standard operating procedure (SOP) to measure the IEC of AEMs is proposed. When compared to conventional acid-base back-titration or Mohr titration, the proposed method combines the fast reaction between silver and halide ions and the accuracy of the potentiometric titration, providing a convenient and precise protocol for researchers in the field.